PEMBUATAN KARBON AKTIF DARI LIMBAH SABUT PINANG ASAL PULAU TIMOR SEBAGAI BIOSORBEN LOGAM Ca DAN Mg DALAM AIR TANAH - Matius Stefanus Batu; Emerensiana Naes; Maria Magdalena Kolo (JURNAL INTEGRASI PROSES, 2022)
The production of activated carbon from areca nut waste as a biosorbent for Ca and Mg in groundwater has been done. This research aimed to determine the ash content, water content, and iodine number of activated carbons from areca nut waste and determine the optimum contact time and adsorption capacity for the adsorption of Ca and Mg in groundwater. Activated carbon making is done by carbonation and activation. The activator used was H2SO4 1,5 M with a soaking time of 24 hours. The adsorption process is carried out in batches with variations in contact time. The results showed that the activated carbon from areca nuts waste had an ash content of 14,97%, water content of 7,17%, iodine number of 1,079.19 mg/g, and the FTIR characterization results showed that activated carbon has the functional groups OH, CH, CO, C≡C, C=C and C=O. The optimum time condition for the adsorption of areca fiber-activated carbon to calcium and magnesium in groundwater is at a contact time of 90 minutes with an adsorption capacity of 2.1196 mg/g for Ca and 0.7540 mg/g for Mg.